Analysis of Immunotherapy in Lung cancer - Burgos-Molina, Antonio Manuel; Alamilla Presuel, Juan Carlos; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (Aseica, 2022)
There are many ways of immunotherapy for lung cancer, and that includes the use of drugs, molecular treatment, and even the combination with radiotherapy. But also, it’s important to investigate in the future the adverse effects of immunotherapy in Lung cancer to avoid breathing complications, and a way to prevent those effects.
Keywords: Inmunoterapia - Congresos; Cancer - Congresos; Immunotherapy; Lung Cancer